Multidimensional Small Baseline Subset (MSBAS) for Two-Dimensional Deformation Analysis: Case Study Mexico City. Issue 4 (4th July 2017) - Samsonov, Sergey V.; d'Oreye, Nicolas
ABSTRACT: Time series of ground deformation are used to describe motion produced by various natural and anthropocentric processes, such as earthquakes, volcanic eruptions, landslides, subsidence due to resource exploitation, and uplift due to fluid injection. Presented here, the multidimensional small baseline subset (MSBAS) technique simultaneously processes multiple ascending and descending DInSAR datasets and produces 2-D, horizontal east-west and vertical, deformation time series with combined temporal resolution over overlapped area. The set of linear equations that comprises MSBAS is usually rank deficient and is solved in the least-square sense by applying the singular value decomposition (SVD) and the zero-, first-, or second-order Tikhonov regularization. The MSBAS source code is written in C++ and is linked to the linear algebra package (LAPACK) library that provides SVD support. For demonstration of capabilities, MSBAS is used to compute 2-D deformation time series of Mexico City by simultaneously processing ascending and descending RADARSAT-2 data acquired during October 2008–December 2012. This area is known to subside due to excessive groundwater extraction that produces pore water pressure drop and compaction of highly compressible clays. During the studied period we observed subsidence with rates over 35 cm/year and horizontal motion of up to 5 cm/year. The MSBAS software can be downloaded fromhttp://insar.ca/ .